Assessing the impact of agricultural technology adoption on farmers' well-being using propensity-score matching analysis in rural China - Wu, Haitao; Ding, Shijun; Pandey, Sushil; Tao, Dayun (Wiley, 2010)
The present paper assesses the impact of improved upland rice technology on farmers' well‐being. The study uses propensity‐score matching to address the problem of ‘self‐selection,’ because technology adoption is not randomly assigned. It applies this procedure to household survey data collected in Yunnan, China in 2000, 2002 and 2004. The findings indicate that improved upland rice technology has a robust and positive effect on farmers' well‐being, as measured by income levels and the incidence of poverty. The effect of technology on well‐being shows a diminishing impact on producers' incomes. This implies that newer innovations are continuously needed to replace older technologies that have reached their saturation points.